Teaching and learning and the curriculum : a critical introduction - Mufti, Emmanuel; Peace, Mark (New York : Continuum, 2012)
Introduction -- Learning theory: conventions and traditions -- Learning theory: new directions -- Intelligence and capacity -- Historical approaches to the curriculum and models of design -- Knowledge, power and ideology -- Knowledge as resistance -- Knowledge and technology -- School ethos and teaching styles -- Conclusion.
Includes bibliographical references (p. [176]-181) and index
EDU
Keywords: Education -- Curricula -- Social aspects; Critical pedagogy; Learning; Constructivism (Education)